2019
DOI: 10.1063/1.5088749
|View full text |Cite
|
Sign up to set email alerts
|

Elastic anomalies associated with domain switching in BaTiO3 single crystals under in situ electrical cycling

Abstract: The elastic response of BaTiO3 single crystals during electric field cycling at room temperature has been studied using in-situ Resonant Ultrasound Spectroscopy (RUS), which allows monitoring of both the elastic and anelastic changes caused by ferroelectric polarization switching. We find that the first ferroelectric switching of a virgin single crystal is dominated by ferroelastic 90° switching. In subsequent ferroelectric switching, ferroelastic switching is reduced by domain pinning and by the predominance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Calculations show that the energy to create 90° domain boundaries is significantly lower than that of their 180° counterparts, [ 63 ] making it more favorable to realize the polarization reversal via two successive ferroelastic switching steps with creation of 90° domain walls, as observed experimentally in single crystals. [ 64 ] In epitaxial films, however, substrate clamping prevents the formation and propagation of these 90° domain walls during switching due to the large elastic energy cost. The removal of this constraint in the membranes—which are only weakly bonded to the silicon substrate—likely permits the local strains generated by 90° domain walls to be readily accommodated thus facilitating a lower‐energy switching process.…”
Section: Figurementioning
confidence: 99%
“…Calculations show that the energy to create 90° domain boundaries is significantly lower than that of their 180° counterparts, [ 63 ] making it more favorable to realize the polarization reversal via two successive ferroelastic switching steps with creation of 90° domain walls, as observed experimentally in single crystals. [ 64 ] In epitaxial films, however, substrate clamping prevents the formation and propagation of these 90° domain walls during switching due to the large elastic energy cost. The removal of this constraint in the membranes—which are only weakly bonded to the silicon substrate—likely permits the local strains generated by 90° domain walls to be readily accommodated thus facilitating a lower‐energy switching process.…”
Section: Figurementioning
confidence: 99%
“…The BTO keeps the 180° domain structure, and a slight movement of the domain wall can be detected when the electric field is smaller than 50 kV cm −1 , as shown in figure 1S iop.org/JPhysCM/31/495702/mmedia). Experimentally, it is reported that the 180° domain wall in the BTO crystals would move at a low electric field which is smaller than that predicted in this work [34]. It is mean that the small electric field should be chosen during the study of the influence of 180° domain wall on the electrocaloric effect in experimental.…”
Section: Resultsmentioning
confidence: 53%
“…Optical microscopy is a simple non-contact method ideal to observe in situ the response of ferroelastic domain walls to temperature [44][45][46][47][48], electric field [48][49][50][51][52][53][54][55][56][57][58][59][60][61] or stress [62,63]. In transmission, the use of crossed-polarizers, combined with a spatial resolution of the order of a half wavelength of light, produces high-contrast images of the domain structure.…”
Section: Polarized Light Microscopymentioning
confidence: 99%